Connection Preeclampsia Incidence With LDH Levels - Ammar Burhanuddin; Masita Fujiko; Dachlia Sri Sakti (Jurnal EduHealth, 2024)
Hypertension is a condition that can affect pregnancy. Preeclampsia is a condition in which hypertension occurs after the 20th week of pregnancy and is accompanied by proteinuria. Lactate dehydrogenase (LDH) is a hydrogen transfer enzyme that catalyzes the oxidation of L-lactate to pyruvate with the intermediary of NAD + as a hydrogen acceptor . This study aims to identify the relationship between the occurrence of preeclampsia with LDH levels . The research was conducted by collecting secondary data from various research journal sources. 20 20 -2024. The research results show that there is connection incident preeclampsia with LDH levels . Lactate dehydrogenase (LDH) undergoes increase in cases preeclampsia . Lactate dehydrogenase useful as marker biochemistry For describe the weight preeclampsia experienced patients . In addition , LDH can also describe possibility emergence complications so that can predict patient prognosis . People in the high lactate dehydrogenase (LDH) group were older and had higher body weight and blood pressure .